Piil Pesenggiri: Modal Budaya dan Strategi Identitas Ulun Lampung - Irianto, Sulistyowati; Margaretha, Risma (UI Scholars Hub, 2011)
Etnifikasi or marginalize the local ethnic as result of migration process in Lampung has caused ulun Lampung’s to became a minority amidst of the cultural heterogeneity immigrants. In response to this marginalization, they re-invented tradition in order to strengthen their collective consciousness through the meaning of piil pesenggiri (self esteem) that's reproduced and articulated as a representation of identity. The study aims to explain how the meaning piil pesenggiri has been reproduced in the repositioning of ulun lampung's cultural identity, related to how ulun lampung interpret piil pesenggiri as a cultural capital and strategy cultural. The data were obtained through in-depth interviews from a number of informants to obtain a comprehensive description of piil pesenggiri based on their experiences in the social world. The results showed that the reconstruction of Lampung ulun identity is inseparable from the development of the political and cultural dynamics in space and time. The production and reproduction of piil pesenggiri as an invention is processed to serve a cultural capital and identity strategy on the social structure vis-a-vis migrants can be viewed as a reteritorialization of identity. Changing the negative stigma that has piil pesenggiri used as cultural